STRATEGY TO CHANGE THE RESEARCH RESULT BECOME MONOGRAPH BOOK - Khasanah, Uswatun; Ika Trisnawati, Septian Nur (Jurnal Indonesia Mengabdi, 2023)
University plays a role in implementing the Tri Dharma of university which consists of Education and Teaching, Research and Development, and Community Service. As a lecturer, social responsibility and professional ethics require lecturers to implement the Tri Dharma of university which not only produces quality scientific contributions but also to ensure that the knowledge produced can be accessed and utilized by society at large. This activity is carried out in order to develop the habit of lecturers to write/compile their own monograph books for the needs of lecturers, students, institutions and the general public. It is hoped that lecturers can develop the ability to write books and have alternative publications for research results and/or community service by this skill. The implementation method used in this service activities is webinars and online mentoring by 203 participants through 3 stages, namely the preparation, implementation and evaluation stages. This service activity is very supportive and able to develop lecturer competence in writing books. This can be seen from the seriousness in following the content of webinar, interaction during the discussion process and the results of the questionnaire shows that 99.02% were satisfied with the implementation of the service and understanding of the material presented.